2013
DOI: 10.1371/journal.pone.0081767
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Roles of the PI3K/Akt Signaling Pathway in Rats with Severe Acute Pancreatitis

Abstract: The phosphatidylinositol 3-kinase(PI3K)/protein kinase B (Akt) pathway plays a key role in inflammation. However, the regulatory roles of PI3K/Akt in severe acute pancreatitis (SAP) have not been elucidated. The aim of this study was to investigate the impact of wortmannin, a PI3K/Akt inhibitor, on SAP rats through exposure to sodium taurocholate (STC) after 3 h and 6 h. The SAP group was found to have a significant increase in pancreas Akt expression, along with the activation of serum amylase, TNF-α, IL-1β, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
(29 reference statements)
1
29
0
1
Order By: Relevance
“…IL-8 stimulates PI3K/AKT pathway, whereas IL-6 and IL-6R combination mainly exert their effects through activation of the JAK/STAT signal transduction pathway, the Ras/Erk, and PI3K signaling pathways. Xu et al 52 have shown that the PI3K/ AKT inhibitor wortmannin decreased inflammatory cytokines in SAP. The PI3K/AKT inhibitor may regulate PI3K/AKT signaling mediated by a reduction in the activation of nuclear factor-κB and p38MAPK activity and the down-regulation of transcription of NF-κB-dependent proinflammatory genes, including TNF-α, IL-1β, and IL-6 in SAP rats.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 stimulates PI3K/AKT pathway, whereas IL-6 and IL-6R combination mainly exert their effects through activation of the JAK/STAT signal transduction pathway, the Ras/Erk, and PI3K signaling pathways. Xu et al 52 have shown that the PI3K/ AKT inhibitor wortmannin decreased inflammatory cytokines in SAP. The PI3K/AKT inhibitor may regulate PI3K/AKT signaling mediated by a reduction in the activation of nuclear factor-κB and p38MAPK activity and the down-regulation of transcription of NF-κB-dependent proinflammatory genes, including TNF-α, IL-1β, and IL-6 in SAP rats.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo tests on rodents (rat paw edema) also suggest that AKT inhibitors prevent AKT phosphorylation and downregulate the expression of inflammatory factors IL-6, MCP-1,TNFα and iNOS [239]. Similarly, in research on pancreatitis, researchers have found that AKT inhibition mediates a reduction in the activation of NF-κB and p38MAPK activity in SAP rats and a downregulation of NF-κB-dependent proinflammatory genes, including TNF-α, IL-1β and IL-6 [240]. …”
Section: Therapeutic Targetsmentioning
confidence: 99%
“…In a rat model of myocardial IRI, pretreatment of erythropoietin led to significant decrease in the levels of proinflammatory cytokines (IL-6, IL-1β and TNF-α). The effects of EPO were found to be associated with the activation of PI3K/Akt signaling, which suppressed the inflammatory responses [42]. Similarly, in a rat model with severe acute pancreatitis, Akt expression in pancreas was significantly increased, along with the activation of cytokines (TNF-α, IL-1β, and IL-6, IL-1β and TNF-α).…”
Section: Pi3k/akt Pathwaymentioning
confidence: 99%